The Application of Benson Relaxation Therapy Technique to Reduce Pain in Post-Cesarean Section Patients in the Mawar Ward of Bengkalis Regional General Hospital - Tuti Qodarsih; Fitra Mayenti; Riski Novera Yenita; Fajar Sari Tanberika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Cesarean section (Sectio Caesarea) is a surgical procedure performed by making an incision in the anterior wall of the uterus to assist the childbirth process. This study aims to examine the application of Benson relaxation technique in reducing the intensity of pain scale in post-cesarean section mothers at Bengkalis Regional General Hospital (RSUD Bengkalis). This research is a quantitative study using a quasi-experimental design. The study was conducted from November to December 2024, involving a sample of 15 respondents. Data were analyzed using univariate and bivariate analysis, with the Chi-Square test applied. All respondents were post-cesarean section mothers. The findings showed that before the intervention, all 15 respondents (100%) experienced severe pain. After receiving the Benson relaxation intervention for 10–15 minutes, a decrease in pain scale was reported. The data indicated that the majority of respondents (86.7% or 13 respondents) experienced a reduction from severe to moderate pain. The statistical test results yielded a p-value of 0.000, indicating a significant effect of Benson relaxation therapy on pain reduction in post-cesarean section patients in the Mawar Ward of RSUD Bengkalis. It is recommended that RSUD Bengkalis consider adopting this technique as an innovation in health services, particularly in nursing care, to help reduce pain in post-cesarean section mothers.